TV 3.0: A Ginga-NCL and Common Core Webservices Extension for Multidevice Support - Oliveira, Karen S. S.; de Macedo, Paulo R. M.; Josué, Marina I. P.; Muchaluat-Saade, Débora C.; dos Santos, Joel A. F. (Anais Estendidos do Simpósio Brasileiro de Sistemas Multimídia e Web (WebMedia), 2023)
Different studies explore the use of second screen devices associated with the content presented on TV. This functionality has been present in the Nested Context Language (NCL) since its proposal as a standard for specifying interactive applications in the Brazilian digital TV system. Despite language support for multiple devices connected to the TV, there is still a lack of a clear definition of protocols for discovery, registration and communication with remote devices. This is the focus of the Guaraná proposal, accepted in the TV 3.0 call. This article extends the Guaraná proposal in order to allow multiple users with their respective HMDs to run the same application. It also generalize the form of communication between Head-Mounted Displays (HMDs) and the middleware Ginga, allowing its reuse by other device types.